Cascade targeting codelivery of ingenol-3-angelate and doxorubicin for enhancing cancer chemoimmunotherapy through synergistic effects in prostate cancer. (January 2022) - Wang, Zhicheng; Sun, Chao; Wu, Haijun; Xie, Jizhen; Zhang, Tong; Li, Yumin; Xu, Xuelian; Wang, Peilin; Wang, Cheng
Abstract: Immunotherapy has led to an expansion of the treatment of malignancies, but its effect in prostate cancer (PCa) patients is modest. Chemoimmunotherapy is a promising approach that has attracted substantial attention. Although the widely used clinical chemotherapeutic drug doxorubicin (DOX) elicits immunogenic cell death (ICD), its weak ICD effect and the abnormal vasculature of tumors severely limit its efficacy in chemoimmunotherapy. Ingenol-3-angelate (I3A), an emerging antitumor drug with dual chemotherapeutic and immune response-eliciting effects, is expected to exert synergistic effects when administered in combination with DOX. I3A induces the ICD of PCa cells by triggering mitophagy and apoptosis and promotes the normalization of tumor vessels, resulting in sufficient infiltration of immune cells into tumors. A synergistic effect of I3A and DOX was observed in vitro at a molar ratio of 1:4. To codeliver this ratio of I3A and DOX to tumor and ensure their uptake, we designed a dual-targeting delivery system, polylactide-poly(ethylene) glycol-2-(3-((S)-5-amino-1-carboxypentyl)-ureido) pentanedioate/triphenylphosphonium (PLA-PEG-ACUPA/TPP), which targets prostate-specific membrane antigen (PSMA) and mitochondria. Delivery of these nanomedicines led to inhibited tumor growth and a strong antitumor immune response. This study sheds light on the mitophagic and antiangiogenic mechanisms underlying I3A treatment of PCa and provides a strategy for combining vascular normalization and chemoimmunotherapy for PCa treatment. Graphical abstract: Image 1